THE ORIGINS OF MANY DISEASES SHOULD BE SEARCHED IN CHILDHOOD - Ровда, Юрий Иванович (Mother and Baby in Kuzbass, 2023)
Professor of the department, doctor of medical sciences, honored doctor of Russia Yuri Ivanovich Rovda talks about the department of pediatrics and neonatology of the Kemerovo State Medical University, its unique team, scientific directions and his own contribution to medical science, pedagogy, and general medicine.